Detección automática de pacientes con arritmias auriculares en registros electrocardiográficos (2021)
The purpose of this research work is the automatic detection of patients with atrial arrhythmias in The purpose of this research work is the automatic detection of patients with atrial arrhythmias using electrocardiographic records, by means of feature extraction and artificial intelligence methods. Taking into account the importance of the analysis of biomedical signals in the development of technologies to prevent, diagnose and treat cardiovascular diseases, which are the main cause of death in the world and in the department of Bolivar, a software is developed in the MATLAB environment, using databases. The selected databases correspond to 49 ECG records of atrial arrhythmias, belonging to patients from the University Hospital of Valencia in Spain and provided by a local researcher.